Effects of Excessive Activation of N-methyl-D-aspartic Acid Receptors in Neonatal Cardiac Mitochondrial Dysfunction Induced by Intrauterine Hypoxia - Liu, Yang; Luo, Ziqiang; Liao, Zhengchang; Wang, Mingjie; Zhou, Yan; Luo, Siwei; Ding, Ying; Liu, Teng; Cao, Chuangding; Yue, Shaojie (Frontiers in Cardiovascular Medicine, 2022)
Intrauterine hypoxia is a common complication during pregnancy and could increase the risk of cardiovascular disease in offspring. However, the underlying mechanism is controversial. We hypothesized that antenatal memantine treatment could prevent heart injury in neonatal offspring exposed to intrauterine hypoxia.Pregnant rats were exposed to gestational hypoxia or antenatal memantine treatment during late pregnancy. Newborns were then sacrificed to assess multiple parameters. The results revealed that Intrauterine hypoxia resulted in declining birth weight, heart weight, and an abnormally high heart weight/birth weight ratio. Furthermore, intrauterine hypoxia caused mitochondrial structural, functional abnormalities and decreased expression of DRP1, and upregulation of NMDAR1 in vivo. Antenatal memantine treatment,an NMDARs antagonist, improved these changes. In vitro, hypoxia increased the glutamate concentration and expression of NMDAR1. NMDAR activation may lead to similar changes in mitochondrial function, structure, and downregulation of DRP1 in vitro. Pharmacological blockade of NMDARs by the non-competitive NMDA antagonist MK-801 or knockdown of the glutamate receptor NR1 significantly attenuated the increased mitochondrial reactive oxygen species and calcium overload-induced by hypoxia exposure. These facts suggest that memantine could provide a novel and promising treatment for clinical use in intrauterine hypoxia during pregnancy to protect the cardiac mitochondrial function in the offspring. To our best knowledge, our research is the first study that shows intrauterine hypoxia can excessively activate cardiac NMDARs and thus cause mitochondrial dysfunction.